DYNAMICS OF MOBILE DEVICE ADDICTION AND COMMUNICATION GAPAMONG COUPLES IN OGUN STATE: THE ROLE OF LANGUAGE - Felicia Tomi OBADARE (CV. ADIBA AISHA AMIRA, 2025)
The widespread incorporation of mobile devices into everyday life has created new challenges in interpersonal interactions, especially among couples. This study investigated the dynamics of mobile device addiction and its effects on communication gaps, emphasising the mediating function of language in Ogun State, Nigeria. The research utilised a descriptive survey design with 110 intentionally chosen couples (N = 220 persons). Data were gathered through a structured questionnaire and analysed utilising Pearson's correlation and Chi-square tests. The findings indicated a substantial positive correlation between mobile device addiction and communication deficits among couples (r = .411, p < .05), implying that excessive mobile usage diminishes emotional intimacy and mutual comprehension. The language employed in mobile- mediated contacts significantly affected relationship comprehension (χ² = .000, p < .05), suggesting that casual, unclear, or emotionally neutral digital language leads to communication failures. The research concludes that language serves as a vital intermediary in the relationship between mobile device addiction and communication quality. These findings underscore the necessity for interventions in communication literacy, the establishment of digital boundaries, and the incorporation of mobile communication dynamics into relationship counseling frameworks. The study recommends that couples should establish consensual guidelines for mobile phone usage during shared activities (e.g., meals, and bedtime) to minimise distractions and improve the quality of face-to-face communication.